PENDAMPINGAN PEMBUATAN KERIPIK SINGKONG PEDAS PADA IBU-IBU PKK PEKON KEPUTRAN - Suyono Suyono; Even Riyadi; Keni Puspita Sari; Wulandari Wulandari (LP3K Lampung, 2020)
In an innovation business, increasing production and marketing is very important in the progress of a company. Small and Medium Enterprises (SMEs) are the most strategic national economic sector and involve the lives of many people so that it becomes the backbone of the National economy. But the problem faced by businesses or small industries today is industrial management and marketing. With community service related to assisting SMEs on traditional types of cassava chips, it is hoped that they can provide solutions to improve SME's welfare. The community service program carried out is by innovating to increase production with a management approach and expanding marketing on social media and modern markets. Small and Medium Enterprises (UKM) Cassava Chips are located in Keputran Village, Sukoharjo District, Pringsewu Regency. This UKM is engaged in the culinary field, namely processing cassava chips snacks with a variety of flavors including spicy, savory, Balado, and original flavors. Ordering cassava chips in UKM is only done through word of mouth, so the order is still small in scope. This is an obstacle for this UKM because it is only in the area around Pringsewu Regency. The method used in this service activity is the collection of activity data using observation and reference methods. Then the result of this service activity is assistance and training in making and marketing via the internet or other social media that can expand market reach and be effective. in ordering products, so that it is not only in the Pringsewu Regency area but also outside the Pringsewu Regency area.